2021
DOI: 10.3390/s21248473
|View full text |Cite
|
Sign up to set email alerts
|

Intracavity Measurement Sensitivity Enhancement without Runaway Noise

Abstract: A method to increase the sensitivity of an intracavity differential phase measurement that is not made irrelevant by a larger increase of noise is explored. By introducing a phase velocity feedback by way of a resonant dispersive element in an active sensor in which two ultrashort pulses circulate, it is shown that the measurement sensitivity is elevated without significantly increasing the Petermann excess noise factor. This enhancement technique has considerable implications for any optical phase based measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 56 publications
(102 reference statements)
0
2
0
Order By: Relevance
“…It has been shown that the sensitivity of such sensors is proportional to the mode spacing of the comb, mode spacing that can be tens of GHz through the insertion of an etalon in the cavity [ 21 ]. Furthermore, because of the comb modes being rigorously equally spaced [ 5 , 28 , 29 ], the resonant dispersion of each Fabry–Perot mode is pasted onto the whole comb structure, resulting in an enhancement of the sensor response [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the sensitivity of such sensors is proportional to the mode spacing of the comb, mode spacing that can be tens of GHz through the insertion of an etalon in the cavity [ 21 ]. Furthermore, because of the comb modes being rigorously equally spaced [ 5 , 28 , 29 ], the resonant dispersion of each Fabry–Perot mode is pasted onto the whole comb structure, resulting in an enhancement of the sensor response [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Depending on its sign, the resonant dispersion affects the phase velocity of the intracavity pulses circulating in the laser, resulting in“fast” or “slow” light. The “fast” light enhances the phase sensitivity of a sensor [ 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%